(untitled) (CIPEEX, 2025)
This paper examines the effects of irregularities occurring during the police inquiry - an administrative, informational stage - on the validity of the criminal action. The aim is to set practical criteria for when investigative defects carry over into the trial, under the pas de nullité sans grief principle (Code of Criminal Procedure, art. 563), which conditions nullity on proof of concrete prejudice. Methodologically, it is a doctrinal and case-law review addressing the prevailing view that defects in the inquiry generally do not contaminate the prosecution, subject to the illicit-evidence exception and its derivatives. The analysis covers common scenarios (unlawful wiretaps; illegal searches and seizures), distinguishing mere investigative illegalities from evidentiary nullities capable of affecting the prosecution when relied upon in court. The findings indicate: (i) defects in the inquiry, by themselves, do not annul the criminal action; (ii) nullification requires a specific nexus between the defect and impairment of defense rights; and (iii) where evidence unlawfully obtained during the inquiry is used at trial, exclusion is mandatory together with an assessment of derivative contamination. The conclusion is that rigorous prejudice review and legality checks on evidence balance investigative efficiency with fundamental guarantees, preventing automatic annulments and promoting substantively just outcomes.